Growth performance, nutrient uptake, and biofortification potential of hydroponic lettuce (Lactuca sativaL.) under calcium supplementation. - Johnson, Chong.; Lavenia, Michael Manus; Chung, Hung Hui; Margaret, Abat; Irna Syarina, Sahari; Loong, Shih Keng; Leonard Lim, Whye Kit (Penerbit Universiti Sultan Zainal Abidin, Malaysia (UNISZA), 2025)
Lettuce (Lactuca sativaL.), a fast-growing and commercially important leafy green, contains about 36 mg of calcium per 100 g. Its calcium content depends on water and nutrient uptake through the roots. This study aims to evaluate how varying calcium levels in hydroponics affectlettuce growth, nutrient absorption, and post-harvest nutrient content, providing insights into optimizing calcium enrichment in lettuce for improved human nutrition. In this study, growth performance, nutrient uptake, and biofortification potential of hydroponic lettuce under varying calcium supplementations of 90, 108, 126 and 144 mg/L were examined. As a result, lettuce fresh weights are significantly higher at 126 and 144 mg/L calcium supplementation. Highest calcium content was found in lettuce hydroponics grown with 108 mg/L calcium (2.35%), potassium and iron are the most abundant nutrients in lettuce hydroponics. Total flavonoid was significantly lowest in lettuce hydroponics cultured with 144 mg/L calcium. Nitrate is found exclusively in in lettuce hydroponics cultured with 144 mg/L calcium. Therefore, it can be deduced that lettuce hydroponics requires at least 126 mg/L calcium, but not more than 144 mg/L calcium for maximal growth, nutrient uptake and nutrient content, as well as safe for consumption.